Group Dynamics of Bina Karya Fish Farmer Group of Milkfish (Chanos Chanos) and Tiger Prawn (Penaeus Monodon) in Kersik Village, Marangkayu District, Kutai Kertanegara Regency - Eko Sugiharto; Gusti Haqiqiansyah; Julia Syahnur Rahmani (Postgraduate, University of Mataram, 2023)
The purpose of this study was to learn about and understand the aquaculture business and the dynamics of the POKDAKAN Bina Karya group inÂ Kersik Village, Marangkayu District, Kutai Kartanegara. This research was carried out for 9 months starting from preparation to research results from August 2022 â€“ June 2023 in Kersik Village. The samples were taken using purposive sampling method. The sampled members of the POKDAKAN Bina Karya with a tenure of membership of 10 years and over. Based on this consideration, out of 30 members, 10 members with a tenure of membership of 10 years and over are taken as a sample. Data analysis was performed using descriptive analysis and Likert scale. The results of the research show that the cultivation business has been going on for 31 years. Cultivation activities are carried out using traditional pond systems and using polyculture techniques involving Milkfish (Channos Channos) and Tiger Prawn (Penaeus Monodon) as the main commodities. The level of group dynamics in POKDAKAN Bina Karya has a cumulative score of 71.9, categorizing it as high (dynamic).